Characteristic and stability of chitosan-based polymer for fruit coating in the presence of ginger essential oil: Effect of acetic acid concentration - Nor Hanuni, Ramli; Nur Syareena Nabihah, Jamaluddin; Siti Nurfazlina, Abdul Rahim; Norhafezah, Kasmuri; Ahmad Fahmi Harun, Ismail (AIDIC Servizi, 2023)
Chitosan-based polymer is ideal for coating fruits in post-harvest treatment to maintain their quality as they can create a film and is biocompatible. The mechanical strength of chitosan (CH) can be enhanced by forming ionic crosslinking between CH molecules through tripolyphosphate (TPP) and surfactants, Tween 80. The presence of ginger essential oil (GEO) increases antimicrobial activity and reduces the swelling of fruit. Selecting appropriate molecular weight of CH, concentration of acetic acid and Tween 80 is necessary for ideal chitosan-based coating properties and stability. This study examined the effect of the parameters on the physicochemical characteristics of final CH-TPP particles. Chitosan-based polymer coating was produced by ionic gelation and the formulated coating solution's particle size and chemical bonding were characterised using Malvern Mastersizer 2000 and Fourier Transform Infrared Spectroscopy (FTIR). The coating on papaya was studied for decay prevention over eight days. The particle size of the formulated coating solutions was found in the 107- 221 nm range. The presence of crosslinking between CH and TPP was observed from FTIR analysis. Good stability of CH-TPP coating was found when utilising high molecular weight chitosan (HMW-CH), the concentration of acetic acid and Tween 80 at 1. 0 % and 0.3 %, respectively. Papaya coated with CH-TPP, and GEO 0.3% had the slowest ripening process during eight-day storage. In conclusion, the formulated CH-TPP with 0.3 % GEO coating was effective for fruit coating applications, especially papaya.